From Tradition to Digital Innovation: The Role of Artificial Intelligence in Driving the Transformation of Islamic Education - Mumtaz, Arina Sabila Aliffiya; Shohib, Muhammad Wildan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Islamic education has a strong tradition of transmitting knowledge through halaqah, Islamic boarding schools, and madrasas, but the acceleration of digital innovation, especially artificial intelligence (AI), encourages changes in the way of learning, teaching, and managing educational institutions to be more adaptive without losing core values. This research aims to compile a systematic review of the role of AI in driving the transformation of Islamic education "from tradition to digital innovation", with a focus on mapping research trends, areas of application (Qur'an Hadith learning, curriculum management, learning personalization), as well as opportunities, risks, and pedagogical ethical prerequisites. The method used is a systematic literature review (SLR) based on the PRISMA guidelines. The article was compiled from Scopus using a Boolean query strategy themed as digital innovation AI transformation digital education in the range of 2021–2025, with open access limitations, empirical articles, and the fields of social sciences and arts and humanities. An initial search yielded 518 articles, filtered into 30, and finally 18 relevant studies were analyzed. The results of the synthesis show a surge in publications in 2025 and the dominant themes include digital leadership, teacher AI literacy, personalization of learning, and governance/ethics (privacy, bias, assessment integrity). In the context of Islamic education, the findings affirm that AI needs to be positioned as a pedagogical partner that strengthens rather than replaces the role of educators, with an emphasis on value protection, equal access, and operational ethical policies. This study recommends a roadmap for value-based AI implementation, strengthening human resource capacity, and a governance framework that secures the quality of religious content and accountability for the use of AI in Islamic educational institutions.